2017
DOI: 10.1513/annalsats.201611-851oc
|View full text |Cite
|
Sign up to set email alerts
|

Readmission to the Intensive Care Unit: Incidence, Risk Factors, Resource Use, and Outcomes. A Retrospective Cohort Study

Abstract: Readmissions to the ICU were frequent and strongly related to poor outcomes. The degree to which ICU readmissions are preventable as well as the main causes of preventable ICU readmissions need to be further determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 32 publications
5
90
1
11
Order By: Relevance
“…The developed model supports several previous studies which identified associations between increased risk of readmission and male gender, older age, admission location and Glasgow coma scale [19,[41][42][43]. Interestingly, previous work found that length of ICU stay was higher among readmitted patients [19,42,43]; however, the present study suggests that if a patient stayed in the ICU one additional day the odds of readmission were decreased by approximately 10%. This finding could be a result of considering a more comprehensive set of administrative and diagnostic variables in a patient's EMR and indicates a potential benefit of prolonging ICU stays.…”
Section: Comparison With Prior Worksupporting
confidence: 89%
See 1 more Smart Citation
“…The developed model supports several previous studies which identified associations between increased risk of readmission and male gender, older age, admission location and Glasgow coma scale [19,[41][42][43]. Interestingly, previous work found that length of ICU stay was higher among readmitted patients [19,42,43]; however, the present study suggests that if a patient stayed in the ICU one additional day the odds of readmission were decreased by approximately 10%. This finding could be a result of considering a more comprehensive set of administrative and diagnostic variables in a patient's EMR and indicates a potential benefit of prolonging ICU stays.…”
Section: Comparison With Prior Worksupporting
confidence: 89%
“…It may be an indicator of poor or incomplete medical care as transfers between healthcare professionals have been linked to an increased rate of adverse events, higher mortality, and hospital stays [15][16][17][18]. If patients at high risk of readmission could be identified, appropriate interventions, such as careful patient evaluation before discharge, planning for proper placement of the patient after discharge, and a safe and thorough handover of patient care between healthcare providers, could be implemented and patient outcomes could be improved [19]. Readmission to the ICU also represents a major source of avoidable costs for the health care system, as up to 30% of total hospital costs and 1% of the US gross national product are directly linked to ICU expenses [20].…”
Section: Introductionmentioning
confidence: 99%
“…They confirmed that unplanned discharges from the ICU during night-time and on weekends were independent risk factors for readmission to the ICU and increased mortality (18,23,24). Others confirmed high age, severity of illness on the day of admission to the ICU and day of discharge from the ICU as well as comorbidities as independent risk factors (8,(25)(26)(27). We did not compare surviving and non-surviving patients after ICU-discharge but non-survivors with or without initial discharge from ICU.…”
Section: Discussionmentioning
confidence: 92%
“…The present study is a post hoc analysis of a retrospective single center cohort study that investigated the impact of ICU readmission on resource use and clinical outcomes [13]. The original study and this post hoc analysis were approved by the Local Ethics Committee at Hospital Israelita Albert Einstein with waiver of informed consent (CAAE:54065716.3.0000.0071).…”
Section: Methodsmentioning
confidence: 99%
“…Multidisciplinary clinical rounds involving ICU physicians, nurses, respiratory therapists, nutritionists, psychologist and clinical pharmacists are performed daily. ICU admissions are made by on-duty intensivists, whereas discharge is a consensus decision-making process involving on-duty intensivists and the primary physician, i.e., the physician who will accept the patient outside the ICU [13].…”
Section: Methodsmentioning
confidence: 99%